THE CONCURRENT PRINCIPAL'S STRATEGY IN DIGITAL LEARNING MANAGEMENT AT SDN 4 BANYURINGIN, KENDAL REGENCY: English - Farid Umar; Iwan Candra Bachtiar; Soedjono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid development of technology in education has compelled schools to embrace digital learning as a vital instructional innovation. However, challenges emerge when school principals must manage multiple responsibilities while ensuring the effective implementation of digital learning. SDN 4 Banyuringin, Kendal Regency, exemplifies a school that has successfully implemented digital learning management strategies despite these constraints. This study, employing a qualitative method with a case study approach, analyzes the strategies of a multitasking school principal in managing digital learning at SDN 4 Banyuringin. Findings indicate that digital learning implementation at the school is effective, positively impacting student learning quality. This success is largely attributed to a delegation strategy involving senior teachers, who, after intensive digital training, serve as mentors to colleagues, facilitating smoother technology adoption. Additional contributing factors include the optimal use of communication technology, support from the education department, infrastructure readiness, and periodic evaluations. Key indicators of effective implementation are increased student engagement, improved material comprehension, and enhanced academic achievement. This study's findings offer a valuable reference for other schools aiming to develop effective digital learning management strategies.